Factors associated with female infertility in Ethiopia: A systematic review and meta-analysis. - Dagne Addisu; Begizew Yimenu Mekuriaw; Besfat Berihun Erega; Wassie Yazie Ferede; Gedefaye Nibret Mihretie; Enyew Dagnew; Assefa Kebie Mitiku; Tegegne Wale Belachew; Maru Mekie (PLoS ONE)
Background Infertility is a significant public health issue that affects couples worldwide. The impacts of infertility is notably higher in Ethiopia due to various factors, such as cultural stigmas surrounding infertility and inadequate infrastructure for diagnosis and treatment. Several fragmented primary studies have assessed factors associated with female infertility in Ethiopia; however, their findings have been controversial and inconclusive. This meta-analysis aimed to identify the factors associated with female infertility in Ethiopia. Materials and methods A comprehensive search was conducted across multiple databases and search engines, including PubMed, African Journals Online, EBSCO, Google Scholar, and the Directory of Open Access Journals. Additionally, studies were searched from the institutional repositories of Ethiopian universities. Data analysis was performed using Stata version 17. The quality of the included studies was evaluated using the Newcastle-Ottawa quality assessment instrument. Heterogeneity and publication bias were assessed using I² and Egger's tests, respectively. A random effects model was employed to identify factors associated with female infertility. The PROSPERO registration number for this meta-analysis was CRD42024525437. Result Six studies were included in the analysis. Factors associated with female infertility included having multiple sexual partners (odds ratio [OR] = 4.31, 95% confidence interval [CI] = 3.46-5.16), a history of sexually transmitted diseases (OR = 2.76, 95% CI = 1.61-3.91), alcohol-abusing partners (OR = 1.57, 95% CI = 1.25-1.89), Khat-abusive partners (OR = 1.85, 95% CI = 1.36-2.35), and women's age over 35 years (OR = 2.07, 95% CI = 1.32-2.81). Conclusion Having multiple sexual partners, a history of sexually transmitted diseases, an alcohol-abusing partner, a khat-abusing partner, and being over the age of 35 were significantly associated with female infertility in Ethiopia. Addressing these risk factors through education, early intervention, lifestyle modifications, and partner involvement can help reduce the burden of infertility and improve the chances of successful conception. The findings underscore the need for further research on understudied factors contributing to female infertility in Ethiopia, including immune function, psychological health, environmental exposures, as well as endocrinological and gynecological conditions.